Calcium sulphoaluminate cement from solid waste with nano-TiO2 addition for high-efficiency CO2 capture. (27th February 2023) - Xie, Jiateng; Yang, Fengming; Tan, Ning; Wang, Weijie; Wang, Wenlong; Wang, Zengmei
Graphical abstract: Highlights: Nano-TiO2 modified the pore structure and increased the adsorption pressure of CO2 . Nano-TiO2 improved ettringite crystallization and crystallization region of CSH. 1% nano-TiO2 led to the formation of concave hexahedrons of ettringite. Abstract: Calcium sulphoaluminate cement from solid waste (WCSA) has a relatively lower sintering temperature and low CO2 emission, meanwhile, the low cost of WCSA and the good CO2 absorption capacity make it one of the current hot topics of research. In this work, based on the optimal water-cement ratio, the effect of titanium oxide (TiO2 ) on the pore structure and the hydration process of WCSA were explored. The hydration process and microscopic evolution were studied by compressive strength test, carbonization test, Brunauer-Emmet-Teller measurement (BET), X-ray diffraction (XRD), the heat of hydration, thermogravimetric analysis (TG), and scanning electron microscope (SEM). The effect of nano-TiO2 on the carbon sequestration behavior of WCSA was also analyzed. The results show that WCSA with a water-cement ratio of 0.4 is the optimal carbonization substrate and nano-TiO2 will make the pore structure more uniform and dense, simultaneously increasing the adsorption pressure for the CO2 . Meanwhile, the nano-TiO2 can effectively promote and regulate the crystallization, nucleation, and growth of ettringite crystals. It can be found that the WCSA containing 1% nano-TiO2 has the highest carbon capture ability among all the contents, and the ettringite crystal is concave hexahedron. The research considered that the concave surface with large specific surface energy can effectively increase the contact area between CO2 and ettringite, which greatly improved the CO2 absorption of ettringite. Overall, WCSA containing nano-TiO2 may provide some new opportunities for efficient carbon capture.